TINGKAT PENGETAHUAN, PERSEPSI, DAN SIKAP MASYARAKAT MUSLIM TERHADAP KEHALALAN OBAT DI DESA SUKARENDAH, SUKARAJA, DAN PADASUKA KABUPATEN LEBAK TAHUN 2024 - Noviyanto, Fajrin; Apriliani, Ade; Stiani, Sofi Nurmay; Shobah, Afifah Nur; Halimatusyadiah, Leni (Universitas Mathla’ul Anwar Banten, 2024)
Halal drugs became a very important issue discussed given th at th ere a re st ill ma ny drugs found that are suspected of containing illegal substances and have not been identified as halal. The aim of this research is to determine the level of knowledge, perception, and public attitude about the validity of drugs and to identify the factors that influence the knowledge, perceived, and attitude of the public about the legitimacy of drugs in the villages of Sukarendah, Sukaraja, and Padasuka. This research uses a descriptive approach model (non eksperimental). On sampling in the population of the village community Sukarendah, Sukaraja, and Padasuka used propability samplings, and collected data through questionnaires. According to the results of the research showed that the level of knowledge about the validity of drugs in the villages of Sukarendah, Sukaraja, and Padasuk very well has a score of 82.86%, the perception of the village people of Skarendha, Sukarasu, and Padasuk to the legitimacy of drugs very good score of 74.29%, the attitude of the people of the towns of Sskarendh, sukaraja and Padassuk very good to the validation of drugs score of 94.3%. Overall, it can be said that the knowledge, understanding, and perception levels of the community of villages are very good.